2004
DOI: 10.1097/01.ju.0000112979.97941.7f
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Sequencing of a Short Course of Androgen Suppression on Freedom From Biochemical Failure When Administered With Radiation Therapy for T2-T3 Prostate Cancer

Abstract: The analysis of study 1 shows a benefit of using a short course of neoadjuvant AS with EBRT vs EBRT alone for localized T2-T3 prostate cancers. Moreover, in each study adding a short course of adjuvant AS after neoadjuvant 1 provided no more advantage in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 15 publications
2
65
0
5
Order By: Relevance
“…Potential advantages of combined modality treatment include an additive or synergistic effect on tumour cell kill and also a reduction in radiation target volume (Dearnaley, 2001). Four phase III randomised trials have reported benefits in tumour control compared to radiation alone (Laverdiere et al, 1997(Laverdiere et al, , 2004Porter et al, 1998;Pilepich et al, 2001), and an overview of the Radiation Treatment and Oncology Groups (RTOG), experience suggested an overall improvement in survival using neoadjuvant androgen suppression in addition to radiotherapy . Several groups have measured the reduction in prostate and prostate target volume after initial hormone treatment, which varied between 25 and 41% and showed a complimentary increase in the sparing of rectum and bladder when initial hormone treatment was combined with CFRT (Zelefsky et al, 1994;Forman et al, 1995;Dearnaley, 2000).…”
mentioning
confidence: 99%
“…Potential advantages of combined modality treatment include an additive or synergistic effect on tumour cell kill and also a reduction in radiation target volume (Dearnaley, 2001). Four phase III randomised trials have reported benefits in tumour control compared to radiation alone (Laverdiere et al, 1997(Laverdiere et al, , 2004Porter et al, 1998;Pilepich et al, 2001), and an overview of the Radiation Treatment and Oncology Groups (RTOG), experience suggested an overall improvement in survival using neoadjuvant androgen suppression in addition to radiotherapy . Several groups have measured the reduction in prostate and prostate target volume after initial hormone treatment, which varied between 25 and 41% and showed a complimentary increase in the sparing of rectum and bladder when initial hormone treatment was combined with CFRT (Zelefsky et al, 1994;Forman et al, 1995;Dearnaley, 2000).…”
mentioning
confidence: 99%
“…30 Two earlier RCTs that included patients with localized PCa who were treated either with RT alone or variable durations of short-term NHT plus RT indicated no advantages to NHT administered for a duration of > 5 months. 7 Finally, 2 more recent trials compared 4 months versus 8 months and 4 months versus 9 months of ADT and RT and found no differences in outcome (Fig. 2).…”
Section: Long-term Adjuvant Adt Plus Rt Versus Adt Alonementioning
confidence: 99%
“…The evidence for short-term NHT plus RT compared with RT alone is supported by several studies. [4][5][6][7][8] In the RTOG 86-10 trial, the combination of goserelin plus flutamide for 2 months before RT and concurrent with RT was evaluated in patients with locally advanced PCa (bulky T2-4 tumors with or without pelvic lymph node involvement). 29 NHT significantly improved diseasespecific survival versus the use of RT alone.…”
Section: Long-term Adjuvant Adt Plus Rt Versus Adt Alonementioning
confidence: 99%
See 1 more Smart Citation
“…Three dimensional conformal radiotherapy (3DCRT) techniques provide the delivery of higher doses to the target while sparing the adjacent normal structures. Additionally, RT and ADT have been shown to improve overall survival (OS), PSA relapse free survival (PSA-RFS) and distant metastasis free survival (DMFS) [1][2][3] compared to RT alone. Thus RT with ADT is the standard of care for localized prostate cancer in intermediate and high risk patients.…”
Section: Introductionmentioning
confidence: 99%